A cyanometallate- and carbonate-bridged dysprosium chain complex with a pentadentate macrocyclic ligand: synthesis, structure, and magnetism. (7th April 2022) - Tan, Pengfei; Yang, Yimou; Lv, Wei; Jing, Rong; Cui, Huihui; Zheng, Shao-Jun; Chen, Lei; Yuan, Aihua; Chen, Xue-Tai; Zhao, Yuyuan
Abstract : A novel one-dimensional polymeric cyanometallate- and carbonate-bridged dysprosium(iii ) chain with a pentadentate macrocyclic ligand exhibits field-induced multiple-relaxation processes. Abstract : A novel one-dimensional (1D) polymeric cyanometallate- and carbonate-bridged dysprosium(iii ) chain with the formula [Dy2 (L N5 )2 Fe(CN)6 (CO3 )(OH)] (1 ), where L N5 is 2, 14-dimethyl-3, 6, 10, 13, 19-pentaazabicyclo[13.3.1]nonadeca-1(19), 2, 13, 15, 17-pentaene, was synthesized, providing the first example of a 3d–4f chain complex based on the combination of cyanometallate- and carbonate-bridged ligands. Single-crystal X-ray diffraction analysis shows that the Dy(iii ) ion is eight-coordinated with the N6 O2 donor set originating from a pentadentate macrocyclic ligand L N5, one [Fe(CN)6 ] 3−, one CO3 2− and OH − . The CO3 2− group bridges two Dy(iii ) ions to form a dinuclear structural unit [Dy2 (L N5 )2 (CO3 )(OH)], which is further linked by [Fe(CN)6 ] 3− ligands to construct an infinite chain. Magnetic studies reveal that the chain complex exhibits two field-induced slow relaxation processes, with the estimated energy barriers U eff = 40.2 and 9.8 K, respectively. This work provides a special strategy for the construction of novel single-molecular magnets and single-chain magnets.